2020
DOI: 10.1186/s11671-020-03361-6
|View full text |Cite
|
Sign up to set email alerts
|

Rh-doped MoTe2 Monolayer as a Promising Candidate for Sensing and Scavenging SF6 Decomposed Species: a DFT Study

Abstract: In this work, the adsorption and sensing behaviors of Rh-doped MoTe2 (Rh-MoTe2) monolayer upon SO2, SOF2, and SO2F2 are investigated using first-principles theory, wherein the Rh doping behavior on the pure MoTe2 surface is included as well. Results indicate that TMo is the preferred Rh doping site with Eb of − 2.69 eV, and on the Rh-MoTe2 surface, SO2 and SO2F2 are identified as chemisorption with Ead of − 2.12 and − 1.65 eV, respectively, while SOF2 is physically adsorbed with Ead of − 0.46 eV. The DOS analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…This limits the number of analytes compatible with pristine TMDs. Hence, a significant effort has been put into the modification of TMDs to enhance their sensitivity toward selected molecules. In the most common approaches, the sheets have been decorated with nanoparticles or single atoms, or they have been doped with single-atom impurities. , Doping has been shown especially effective in enhancing the values of adsorption energy and charge transfer for nitrogen and sulfur-containing gases, as well as other compounds including formaldehyde (CH 2 O), , ethylene oxide (C 2 H 4 O), and histamine (C 5 H 9 N 3 ) . However, the reported values often indicated that the doping facilitated strong chemisorption.…”
mentioning
confidence: 99%
“…This limits the number of analytes compatible with pristine TMDs. Hence, a significant effort has been put into the modification of TMDs to enhance their sensitivity toward selected molecules. In the most common approaches, the sheets have been decorated with nanoparticles or single atoms, or they have been doped with single-atom impurities. , Doping has been shown especially effective in enhancing the values of adsorption energy and charge transfer for nitrogen and sulfur-containing gases, as well as other compounds including formaldehyde (CH 2 O), , ethylene oxide (C 2 H 4 O), and histamine (C 5 H 9 N 3 ) . However, the reported values often indicated that the doping facilitated strong chemisorption.…”
mentioning
confidence: 99%
“…Though NO 2 had a higher adsorption energy, it exhibited the highest recovery time of 222 s and 1800 s on S and Se sites, respectively, at 300 K. However, this recovery time at room temperature was comparable with other reported values of NO 2 sensing, which range in the order of 10 2 –10 3 s. 37,56,62 Yet, this recovery time would be controlled when the temperature rises because it varies with the working temperature. 37,56,62,63 Also, the recovery times of 47.1/29.5 ms and 5.76 ms/1.30 s on S and Se sites, respectively, for NO/SO 2 make MoSSe credible for reprocessing in several seconds while performing NO and SO 2 detection. The recovery time for NH 3 , HCN, CO 2 , CO and H 2 S gases detection was in the order of μs, which indicated a good response in the desorption process of these gases from the monolayer.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Zhu, H.L. and others (Zhu et al, 2020) explored the gas-sensing properties of Rh-MoTe 2 for SF 6 decomposition products based on first-principles, and found that Rh-MoTe 2 monolayer showed good adsorption performance for SOF 2 . Jiang et al (2022) chose the metal ruthenium with high chemical activity as the doping element, and calculated the adsorption of SF 6 decomposition products on Ru-MoTe 2 monolayer based on density functional theory, the adsorption capacity of the system to the decomposition products was significantly improved after Ru doping.…”
Section: Additive Dopingmentioning
confidence: 99%